Pengukuran Kepuasan Pelanggan Terhadap Layanan Bidang Akademik Politeknik Negeri Semarang - Budhi Adhiani C. (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2018)
The purpose of this study was to measure customer satisfaction levels of academic services Semarang State Polytechnic (POLINES) in 2016, for any study program as well as overall POLINES, then compared it with the level of satisfaction in 2012, 2013, 2014 and 2015. Types of academic services measured including services : re-registration ; licensing ; access of exam result; guidance from academic guardian; compensation; scheduling lectures; implementation of semester exam; implementation of field study course and field work service implementation. Academic service determination of the satisfaction attributes level was conducted by testing validity and reliability with Spearmen correlation coefficient and Cronbach's Alpha . Measuring the level of satisfaction of academic services had done by calculating the average level of satisfaction measured directly. Respondents were 440 students from 22programs of study at the Polytechnic of Semarang using purposive sampling. The results of this study are : 1) The level of academic services satisfaction at Semarang State Polytechnic as overall was satisfactory . There were 5 types of academic services available at the satisfactory level, the guidance from academic guardian services, the scheduling lecture services, the implementation of semester exam services, the implementation of field study course, and field work service implementation ; 2) Study Program of Civil Construction Technique at the highest level of satisfaction academic services ( 3,80 ), while the Accounting Managerial Study Program at the lowest level of satisfaction (2,98) ; 3) The implementation of field study course services type at the highest level of satisfaction ( 3.71 ) , while the type of exam result access services at the lowest level of satisfaction ( 3.10 ); 4) There were 11 study program which the level of customer satisfaction on academics field services were increasing compared to 2015, namely study program of Informatics and Computer, Telecommunications D4, Civil Engineering, Energy Conservation, Syariah Banking, International Business Management, Bridges and Roads Planning, Building Maintenance and Repairment, Production and Maintenance Engineering, Business Administration D4. At the same time, the academics field services compared to 2015 were Civil Contruction Technique Study Program. 5) The level of customer satisfaction on academic field services in 2016 in every type of services were increasing compared to 2015. There were 4 types of services, licensing services, access of exam result services, ; guidance from academic guardian services, implementation of semester exams, The implementation of field study course services; 6) The level of customer satisfaction on academic field services in 2016 in every type of services, there were 2 types services which were the same compared to 2015, re – registration services and scheduling lectures services.Suggestions for improving the quality of academic services Semarang State Polytechnic is as follows : Improving the quality of service priority in access of exam result service